Structuralism in believable criticism Kamal Abu Dib is an example - Halluom, Ahlam (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
In this research I studied structural concepts , and how to move into the Arabic cultural field. I defined these concepts, and the most important people who founded it and contributed to its construction as a structural approach . Then I traced the ways that brought it to the modern Arabic criticism .And the role of competency in the process of vulnerability and influence. Perhaps the practical steps I have taken has made the structural approach take its obvious features in our Arabic criticism. This research is presented in detail by the structural critic Kamal Abu Dib , through his structural applications. And because it is impossible to take note of all structural aspects that resembled the archipelago to look up from the top, I tried to study structuralism as a way of thinking and literary criticism. In particular ,structuralism seeks to discover the relationship between the literary system ( the text ) and the culture , that the text part of it.